Analisis Rechtsvacuum dalam Hukum Acara Pidana Indonesia: Penerapan Penghentian Penuntutan Berdasarkan Keadilan Restoratif - Arnott Ferels; Hery Firmansyah (Syntax Corporation, 2023)
Within the context of criminal procedural law in Indonesia, the Criminal Procedure Code (often referred to by its Indonesian acronym, KUHAP) serves as the primary normative foundation governing the prosecution process. While the KUHAP intrinsically emphasizes a retributive justice paradigm, the global legal thought trend is currently shifting towards restorative justice (RJ). A crucial element in the KUHAP that warrants further scrutiny in this context is the prosecutorial discretion concerning the discontinuation of prosecutions. This research zeroes in on the analysis of the legal void or rechtsvacuüm in relation to RJ within the KUHAP, encompassing a comparative study with RJ models applied in various jurisdictions, such as the United States, the Netherlands, Japan, and Germany. The primary objective is to identify aspects of the KUHAP, especially those related to prosecutorial discretion, that have the potential to be harmonized with RJ principles, thereby supporting the restoration of relationships among offenders, victims, and the community. The findings from this analysis are hoped to inspire a more adaptive and inclusive reform of the criminal justice system in Indonesia. As recommendations, this research suggests the formulation of more explicit regulations, enhancement of the capacity of law enforcement officers through education and training, and collaboration with countries that have a proven track record in implementing RJ.